2012
DOI: 10.1108/09593841211232677
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of free/libre open source software in public organizations: factors of impact

Abstract: Purpose -In this paper the authors aim to investigate the importance of factors for the adoption of free/libre open source software (FLOSS) in the public sector. They seek to evaluate how different factors impact during the initiation and implementation phases of the adoption process. Design/methodology/approach -The authors base the methodological approach on two exploratory case studies with a contrasting result logic. They build a multi-level framework grounded both on literature review, and feedback from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 39 publications
0
38
0
7
Order By: Relevance
“…Additional studies from 2006-2013 period complement the findings on FLOSS implementation enablers and inhibitors (Ven and Verelst, 2006;Morgan and Finnegan, 2007;Gallego et al, 2008;Sohn and Mok, 2008;Lee et al, 2009;Hauge et al, 2010;Nagy et al, 2010;Rossi et al, 2012;Li et al, 2013). In Ven and Verelst's study (2006), five case studies are reported from Belgian organizations that adopted the utilization of a FLOSS operating system.…”
Section: Review Of Studies On Floss Success-failure Implementation Famentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies from 2006-2013 period complement the findings on FLOSS implementation enablers and inhibitors (Ven and Verelst, 2006;Morgan and Finnegan, 2007;Gallego et al, 2008;Sohn and Mok, 2008;Lee et al, 2009;Hauge et al, 2010;Nagy et al, 2010;Rossi et al, 2012;Li et al, 2013). In Ven and Verelst's study (2006), five case studies are reported from Belgian organizations that adopted the utilization of a FLOSS operating system.…”
Section: Review Of Studies On Floss Success-failure Implementation Famentioning
confidence: 99%
“…The main found inhibitors were: switching costs (called sunk costs), project forking, lack of internal expertise, hard selection process (reported as knowledge barriers), legacy integration, and technological immaturity. In turn, Rossi et al (2012) investigated two Italian governmental organizations as case studies. These investigators found the following main enablers: positive attitude to change (akin new business opportunities in private sector), top management support, employee skill and training, and implementation champion.…”
Section: Review Of Studies On Floss Success-failure Implementation Famentioning
confidence: 99%
“…Others focus on specific contexts; for example, both Rossi et al [42], and Fitzgerald et al [14] present frameworks to explain FOSS adoption in the public sector. Eckhardt et al studied the impact of social influences, referring to the influences of colleagues and other departments in an organization [12].…”
Section: Explaining Adoption Of New Toolsmentioning
confidence: 99%
“…[40]); others are based on a set of factors that have been identified a priori before any feedback is solicited from experts (e.g. [42]). While these approaches are not invalid, they ignore perhaps the most important stakeholders, namely the volunteers adopting the technology.…”
Section: Explaining Adoption Of New Toolsmentioning
confidence: 99%
“…Some of them (for instance Navica (Golden, 2005) and QMOSS (Sung et al, 2007)) are simple models composed for 5-7 single factors and 3-5 steps, and others are complex ones with over 10-15 steps and 60 evaluation items (QualiPSo (del Bianco et al, 2009) andQSOSv2 (QSOS.org, 2013)). Additionally, other studies have identified a set of organizational factors associated to successful and failed utilizations of FLOSS tools in organizations (Dedrick and West, 2003;Rossi et al, 2012;Li et al, 2013), which provide also useful information to avoid failed and wrongly FLOSS evaluations. Hence, while FLOSS has been used for large companies, we consider that FLOSS is a natural logical resource to be used for small and medium-sized companies, which have more budgetary and human resource limitations for using commercial software (Tribunella and Baroody, 2007).…”
Section: Introductionmentioning
confidence: 99%